A Comparison of the Glasgow Coma Scale Score with Full Outline of Unresponsiveness Scale to Predict Patients' Traumatic Brain Injury Outcomes in Intensive Care Units. (10th June 2014) - Jalali, Rostam; Rezaei, Mansour
Abstract : Background . Neurological assessment is an essential element of early warning scores used to recognize critically ill patients. We compared the performance of the Glasgow Coma Scale (GCS) with Full Outline of Unresponsiveness (FOUR) scale as an alternative method in the identification of clinically relevant outcomes in traumatic brain injury. Objective . The purpose of this study was to compare the performance of GCS with FOUR scale. Methods . For this study 104 patients with brain injury were recruited from the ICU of Taleghani Hospital, a major teaching hospital in Kermanshah in the western part of Iran. Data was collected concurrently from the ICU admissions by three well-educated nurses and then checked for accuracy by the researcher. Patients were followed up until two weeks or hospital discharge to record their survival status. As a final point expected risk of mortality was calculated using the original formulas for each scale. Results . The mean age of 104 participants was 41.38 ± 18.22 (rang 17 to 86 years) mostly (81 patients 77.9%) males. The FOUR scale has a better prediction for death than GCS. Conclusion . It appears that FOUR scale had better predictive power for mortality and may be a suitable alternative or complementary tool for GCS.